Body mass index affects kidney transplant outcomes: A cohort study over 5 years using a steroid sparing protocol - Bellini, Maria Irene; Deurloo, Emily; Consorti, Fabrizio; Herbert, Paul Elliot (Frontiers in Endocrinology, 2023)
Background: There is controversy regarding the suitability of high body mass index (BMI) candidates accessing the transplant waitlist. Patients and Methods: Observational study on consecutive kidney transplant recipients undergoing surgery between January 2014 and March 2016 at our centre. Patients were stratified according to BMI. Survival outcomes and graft function were analysed to investigate the effect of donor’s and recipient’s demographic characteristics. Results: 396 kidney transplant recipients: 260 males, mean age 51.8 ± 15.9 years, followed up for a mean time of 5.86 ± 2.29 years. Mean BMI 26.2 ± 5.1. BMI class 1 (20 ≤ BMI ≤ 24.9) n=133, class 2 (25 ≤ BMI ≤ 29.9) n= 155, class 3 (30 ≤ BMI ≤34.9) n=53, class 4 (BMI ≥ 35) n=21), class V (BMI ≤ 19.9) n=34. Patient survival was not significantly different according to the recipient’s BMI class (p=0.476); graft survival was affected (p=0.031), as well as graft function up to 2 years post-transplant and at 4 years follow up (p=0.016). At logistic regression the factors independently associated with graft loss were only donor’s age (p=0.05) and BMI class of the recipient (p=0.002). Conclusions: Obesity did not impact on patient’s survival but affected graft function and graft loss.